EKSISTENSI POLITIK PEREMPUAN ACEH MENJELANG PEMILIHAN UMUM (PEMILU) 2024 - Zuriah Zuriah; Teuku Amnar Saputra (STISNU Aceh, 2022)
Islam sees that women are not only domestic creatures (home) who are not allowed to enter and participate in the public (political) sphere. Men and women are given the same rights to contribute in all fields whether social, political, legal, technological development, and so on. Based on this background, this study tries to analyze the position of Acehnese women's groups and their existence ahead of the 2024 elections. This research was conducted using a historical approach (Historical Approach). The historical approach was taken in order to trace the history of women's participation in politics in Aceh from time to time by analyzing descriptive, comprehensive, holistic and complete data. The results of this study indicate that: First: The history of women's participation in politics in Aceh is demonstrated by the central role of a number of female figures in formal politics in the region. Historically, Acehnese women, apart from having the ability to lead and govern, also had significant influence from a political perspective, which succeeded in providing protection and legal certainty to women. Second: The political existence of Acehnese women ahead of the 2024 election is very inclusive. UUPA as legal legality is more progressive because it guarantees gender equality in it, and even explicitly guarantees the protection and equality of women. Even so, there are many gaps in women's ideology that raise their own challenges for Acehnese women's practical political candidates in the upcoming 2024 general elections.